Community structure of caterpillar parasitoids from tropical rain forest - Libra, Martin (Jihočeská univerzita, 2021)
The aim of this dissertation is to investigate the community structure of parasitoids and their interactions with their hosts - caterpillars in the rainforest of Papua New Guinea, focusing on beta diversity and altitudinal trends. We show that parasitoid beta diversity is higher than the beta diversity of their hosts, which was also projected in their interactions. The altitude plays important role in the diversity of parasitoids, where we show that Ichneumonidae are more diverse at high elevation than at low elevation, which was not observed for other large insect families. Further, we performed a manipulative experiment, exposing live caterpillars in different elevations of tropical rainforest. Caterpillars faced similar mortality from parasitoids between elevations, but higher mortality from predation at low elevation. In the last chapter, we point out how important is correct species identification because wrong identification can misinterpret observed interactions.
Community structure of caterpillar parasitoids from tropical rain forest
Keywords: parasitoid; diversity; beta diversity; altitudinal gradient; taxonomy; Ichneumonidae; Braconidae; Tachinidae; food-web interactions; parasitoid; diversity; beta diversity; altitudinal gradient; taxonomy; Ichneumonidae; Braconidae; Tachinidae; food-web interactions